Optimizing Employee Performance Through Competency - Butarbutar, Herawati; Isa Indrawan, Muhammad (PT. Multidisciplinary Press Indonesia, 2024)
This research aims to see the effect of communication on employee performance with competency as an intervening variable at BPJS Employment Padang Sidimpuan Branch and BPJS Employment Kisaran Branch. The phenomenon that occurs at BPJS Employment in the Padang Sidimpuan Branch and Kisaran Branch is the influence of communication on employee performance and work competency. Because there are still many individuals who lack the ability to comprehend and understand communication, the effectiveness of communication cannot run smoothly. When an individual sends a message in communication, the recipient of the message must understand the meaning of the message so that employee performance and competence can run well with the aim of achieving the success of a company. The results of this research are as follows: Competency has a positive and significant effect on employee performance with a value of 0.604 and a significant value of 0.000. Communication has a positive and significant effect on employee performance with a value of 0.307 and a significant value of 0.001. Communication has a positive and significant effect on Competency with a value of 0.768 and a significant value of 0.000. Communication has a positive and significant effect on employee performance indirectly through Competency with a result of 0.463 and a significant value of 0.000.